Application of CK-12 on Bacterial Topic Constructed on Inquiry Based Learning to Enhance Critical Thinking Ability of 10th Grade High School Students - Carolina Adventia Kriswanti; Endang Susantini (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2023)
The availability of learning media that facilitates the needs of students to enhance critical thinking skills in integration with ICT is still very limited nowadays. Bacteria are still considered as materials that are difficult for 10th graders to understand and master. Various uses of bacteria in the surrounding life are also difficult to understand. Therefore, it is necessary to apply a Learning Management System that is integrated with critical thinking skills training. Inquiry-Based Learning is a relevant learning model integrated in improving students' critical thinking skills on the topic of bacteria. This study aims to apply the CK-12 constructed on Inquiry-Based Learning as a practical, straightforward, and easy-to-use learning instrument to enhance critical thinking skills. This study uses the ADDIE research model amount to analysis of curriculum, students, concepts, and assignments; design and development on CK-12 platform; implemented in the classroom for 3 weeks; and evaluated on every phases mentioned, accompanied by validation method, implementation observation, and student response questionnaire method which was carried out on 85 grade 10th students of SMAK Untung Suropati Sidoarjo and the data obtained were analysed using descriptive-quantitative techniques. This study resulted in the application of the CK-12 with a validity score of 3.8; the implementation of learning is 83.69; and the positive response of students was 92.89%. Thus, the application of CK-12 on bacterial topic constructed on Inquiry-Based Learning to enhance critical thinking skills for 10th grade high school students is very feasible in terms of validity, implementation, and student responses. Keywords: CK-12, bacteria, inquiry-based learning, critical thinking skills.